Turning the tide on drought in Jordan, Lebanon and Morocco - Palay, Isis (International Water Management Institute, 2022)
The blog is about the work of the International Water Management Institute (IWMI), CGIAR, and its many Research Centers towards scaling up the deployment of water-smart agricultural solutions to slow the march of land degradation and desertification, and enhance the resilience of vulnerable populations to droughts.